Evolution of doctor shopping for oxycodone in the 67 million inhabitants in France as a proxy for potential misuse or abuse. Issue 3 (March 2021) - Soeiro, Thomas; Pradel, Vincent; Lapeyre-Mestre, Maryse; Micallef, Joëlle
Abstract : Abstract: This nationwide study aimed to compare use of oxycodone and doctor shopping for oxycodone in 2010 and 2016, and to quantify doctor shopping for oxycodone by sex, age, formulation, and dosage in 2010 and 2016. This study is a cross-sectional comparative analysis of doctor shopping based on all dispensings of oxycodone in France, in 2010 and 2016. Dispensings of oxycodone were extracted from the Système national des données de santé, which covers the 67 million inhabitants in France. Quantification of doctor shopping relies on an algorithm accounting for overlapping prescriptions, which is a proxy for potential misuse or abuse. The number of subjects who received oxycodone increased by 214% from 67, 838 subjects in 2010 to 212, 753 subjects in 2016, and the number of subjects with doctor-shopping behavior increased by 197%, from 1066 subjects in 2010 to 3163 subjects in 2016. For 30- to 44-year-old men, the total quantity of oxycodone obtained by doctor shopping increased by 391%, from 4582 defined daily doses in 2010 to 22, 517 defined daily doses in 2016. By formulation and dosage, the total quantity of oxycodone obtained by doctor shopping increased with the dosage for both immediate-release and extended-release tablets in 2010 and 2016. The widespread extent of doctor shopping and its 3-fold increase in line with population exposure is a strong signal in the French context. These results are another argument to avoid trivializing oxycodone to prevent misuse, potential abuse, and potential oxycodone-related deaths, but it requires caution to prevent compromising effective treatment of pain. Abstract : Supplemental Digital Content is Available in the Text.In France, from 2010 to 2016, there was a 3-fold increase of doctor shopping for oxycodone in line with population exposure, with more doctor shopping in adult men and for higher dosages.